Comparison of vasorelaxant effect and tolerance profile of a novel isosorbide-5-mononitrate derivative with its stereoisomer and parent drug on rat mesenteric artery - Stepanović-Petrović, Radica M; Savić, Vladimir; Tomić, Maja A.; Tokic-Vujošević, Zorana; Simić, Milena; Stepanović, Jelena M.; Jokanović, Milan; Micov, Ana (Arzneimittelforschung, 2010)
5-Ketoximeisosorbide-2-mononitrate (5O-IS-2-MN) was synthesized and its pharmacological and texicological characteristics were examined and compared with its parent drug, isosor-bide-5-mononitrate (IS-5-MN, CAS 16051-77-7), and its diastereoisomer 2-ketoximeisosorbide-5-mononitrate.Vasorelaxation was studied on phenylephrine-precontracted rat superior mesenteric artery rings in organ bath procedure. In some rings, the endothelium was mechanically removed. In vitro tolerance was induced by treating the precontracted rings with maximal concentrations of the parent drug and the ketoximes, and after washing out, the procedure was repeated for two times. Furthermore, rats were treated with a single oral dose (1000 mg/kg) of 5O-IS-2-MN and 2O-IS-5-MN.After a phenylephrine-induced contraction, 5O-IS-2-MN (10−8–10−4 mol/l) caused a concentration-dependent relaxation of the rat superior mesenteric artery that was strongly potentiated after the removal of the vascular endothelium. In preparations with or without endothelium, 5O-IS-2-MN was a more potent relaxant than either the parent compound or its isomer. The mechanism of the relaxant effect of 5O-IS-2-MN involves the activated soluble guanylyl cyclase-cyclic GMP pathway. Hydralazine (10−5 mol/l), a strong antioxidant, ameliorated tolerance to IS-5-MN, but did not affect the absence of tolerance to either ketoxime. The minimum lethal dose in rat for 5O-IS-2-MN and 2O-IS-5-MN was greater than 1000 mg/kg.These results suggest that the modification of the configuration at the ester carbon of IS-5-MN contributes to more potent and tolerance-devoid activity on the rat superior mesenteric artery.
Keywords: Endothelium; Hydralazine; 5-Ketoximeisosorbide-2-mononitrate; Nitrate tolerance; Organic nitrates